2002
DOI: 10.4049/jimmunol.169.11.6467
|View full text |Cite
|
Sign up to set email alerts
|

Resident Cell Chemokine Expression Serves as the Major Mechanism for Leukocyte Recruitment During Local Inflammation

Abstract: The mechanistic relationships between initiating stimulus, cellular source and sequence of chemokine expression, and leukocyte recruitment during inflammation are not clear. To study these relationships in an acute inflammatory process, we challenged a murine air pouch with carrageenan. A time-dependent increase in TNF-␣, monocyte chemottractant protein-1 (MCP-1), macrophage-inflammatory protein-1␣ (MIP-1␣), RANTES, KC, and MIP-2 was found in the exudates preceding cell recruitment, but displaying different ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 46 publications
11
149
1
5
Order By: Relevance
“…We observed that cell culture supernatants collected from isoprenaline-stimulated neutrophils initiated chemotaxis in neutrophils from both males and females. This effect was antagonized, in females, by SB225002, a selective CXCR2 antagonist, and by a CXCR2 antibody, which has been shown to markedly inhibit IL-8-induced neutrophil migration in murine models of inflammation (Garcia-Ramallo et al, 2002). However, while b 2 -adrenergic receptor agonists can increase IL-8 production (Linden, 1996;Kavelaars et al, 1997;Prause et al, 2003), this did not appear to be the mechanism of isoprenaline-induced chemotaxis in our study.…”
Section: De Coupade Et Alcontrasting
confidence: 61%
“…We observed that cell culture supernatants collected from isoprenaline-stimulated neutrophils initiated chemotaxis in neutrophils from both males and females. This effect was antagonized, in females, by SB225002, a selective CXCR2 antagonist, and by a CXCR2 antibody, which has been shown to markedly inhibit IL-8-induced neutrophil migration in murine models of inflammation (Garcia-Ramallo et al, 2002). However, while b 2 -adrenergic receptor agonists can increase IL-8 production (Linden, 1996;Kavelaars et al, 1997;Prause et al, 2003), this did not appear to be the mechanism of isoprenaline-induced chemotaxis in our study.…”
Section: De Coupade Et Alcontrasting
confidence: 61%
“…TNF-␣ is also a known chemotactic factor for neutrophils (46,47), and both activates endothelial cells and increases the expression of adhesion molecules (48, 49) further promoting leukocyte transmigration. Increased levels of TNF-␣ can be detected as early as 2h after the carrageenan injection in air pouches and precede the neutrophilic infiltration (50), supporting the concept of a key role in chemoattraction of these cells (47). Pouch lining macrophages, mast cells and fibroblasts contribute to the early levels of TNF-␣.…”
Section: Discussionmentioning
confidence: 73%
“…The nature of extravasation kinetics (25) and interplay between the different subsets remains unclear (26,27). We examined the effect of neutrophils on the recruitment of CD11b + Ly-6C int Ly-6G 2 cells to the dermis in CX3CR1 +/GFP mice.…”
Section: Resultsmentioning
confidence: 99%
“…Upon disruption of homeostasis, the content of the inflammatory cell infiltrate must be tightly regulated. It is widely accepted that neutrophils infiltrate the lesion first and are swiftly followed by MOs, although the role played by neutrophils in the control of MO recruitment is unclear (26,27,41). The poor specificity of anti-Gr1 (Ly-6C/Ly-6G) Ab has contributed to confusion in the field.…”
Section: Discussionmentioning
confidence: 99%